The EFFECT OF ADDITIONING PALM MUSHROOM (VOLVARIELLA VOLVACEA) AND MORINGA LEAVES (MORINGA OLEIFERA) TO INCREASE THE VALUE OF FUNCTIONAL FOOD ON CRY NOODLES - Andwini Prasetya (Jurnal Agroindustri Pangan, 2025)
Palm mushrooms and Moringa leaves contain nutrients and non-nutritional substances so they can be used as functional foods to support a person's daily diet. The protein and fiber content in palm mushrooms and Moringa can be said to be quite high. The use of palm mushrooms and Moringa is expected to increase the protein and fiber content of noodles. This study aims to determine the production resulting from the addition of palm mushrooms and Moringa leaves and the chemical content of dry noodles consisting of water, protein and fiber content. The study design used a Completely Randomized Design (CRD) consisting of 2 treatments: the addition of palm mushrooms consisting of 3 factors: 15%, 30%, 45% and the addition of Moringa leaves consisting of 2 factors: 20%, 40% so that it becomes 6 treatments. The higher the Moringa leaves added, the higher the percentage of dry noodle yield, the yield ranges from 65.0% to 65.5%. The quality of the water content of protein and water content of dry noodles with the addition of palm mushrooms and Moringa leaves between 4.19% - 5.08% has met SNI. Meanwhile, the highest protein content was 9.81% in the 30% palm mushroom and 40% moringa leaf treatment, and the highest fiber content was 1.93% in the 30% palm mushroom and 20% moringa leaf treatment.